MULTIKULTURALISME DAN PENDIDIKAN NILAI DALAM PEMBELAJARAN SEJARAH - Musa Pelu; Isawati Isawati (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
The long-term goal of this research is that in Surakarta, multicultural social stability can be established far from a culture of violence, especially between ethnic Chinese and Javanese. This is considering that the target of the the violence cases that occurred in Surakarta was ethnic Chinese. The method developed was optimiz-ing the education of multiculturalism values in historical learning in SMA / SMK Surakarta. The specific objective of this research was to obtain scientific data on multiculturalism and value education in history learning in high school / vocational school in Surakarta. This study uses a naturalistic approach to describe naturally, completely, deeply, and intactly about multiculturalism and value education in historical learning in high school / vocational high school in Surakarta. Therefore, this research is exploratory, which explains a phenomenon that is detailed, comprehensive and in-depth. Data collection techniques include direct observa-tion, in-depth interviews, archival studies, historical analysis, and FGD. The conclusions of this study are as follows: (1) most of the history teachers in high school / vocational school do not fully understand the concept of multiculturalism and the implementation of its values in historical learning, (2) the history teachers in high school / vocational schools have a positive perception and support the implementation of multiculturalism values in history learning , (3) in the learning process, the teachers have tried to implant multiculturalism values, such as values of tolerance, democracy, cooperation, unity, and the value of peace in learning history. The values of multiculturalism have also been included in the RPP of the history subjects, as one of the basic competencies, (4) the students have a positive perception and agree to the planting of the multiculturalism values in learning history. They consider that the planting of multiculturalism values can support the realization of national unity.